Extract of Euterpe oleracea Martius Stone Presents Anticonvulsive Activity via the GABAA Receptor - Muto, Nilton Akio; Hamoy, Moisés; da Silva Ferreira, Chryslen Brenda; Hamoy, Akira Otake; Lucas, David Cristian Rodrigues; de Mello, Vanessa Jóia; Rogez, Hervé (Frontiers in Cellular Neuroscience, 2022)
Epilepsy is one of the most common neurological diseases globally, resulting from a disorder in brain activity. This condition can be triggered by birth trauma, traumatic brain injury (TBI), infections of the brain and stroke. More than 70 million people suffer seizures caused by neurological abnormalities. Approximately 80% of all epileptic patients reside in low-income conditions or in developing countries, and over 75% of patients do not receive proper treatment. Our previous study found an anticonvulsant property of an extract of Euterpe oleracea stone (EEOS) that caused myorelaxation, sedation, and cardiac and respiratory depression after intraperitoneal administration. The present study investigated through electroencephalographic (EEG) profiling the anticonvulsant protective properties of EEOS in induced convulsing rats. Male Wistar rats were treated with EEOS (300 mg/kg), diazepam (DZP) (5 mg/kg), pentylenetetrazol (PTZ) (60 mg/kg) and flumazenil (FMZ) (0.1 mg/kg) by intraperitoneal (i.p.). Electrodes implanted on the dura mater provided EEG data in which EEOS suppressed seizure deflagration caused by PTZ. In addition, EEOS presented no significant difference in comparison to DZP, which has the same mechanism of action. After FMZ injection, a GABAA receptor antagonist blocked the anticonvulsive effect in both the DZP and EEOS groups, suggesting that EEOS exerts it action on the GABAA receptor at the benzodiazepine (BDZ) subunit.